1989
DOI: 10.1159/000263388
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tissue from Spontaneous Abortions: A New Alternative for Transplantation Research?

Abstract: While transplantation of fetal tissues may alleviate a great deal of suffering, current policy bars federal funding of research using tissue from elective abortions. Using fetal tissue from spontaneous abortions would obviate the moral concerns. If existing studies of small samples are extrapolated to the US population, then each year about 750,000 fetuses are aborted spontaneously by week 28 (500,000 in the first trimester and 250,000 in the second trimester). The consensus among researchers is that spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The mean maternal age was 32.2 years (range 25-43), and the mean gestational age was 18 weeks (range [13][14][15][16][17][18][19][20][21][22]. The recorded mean in terval between abortion and death was 8 min (range 1-18) (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean maternal age was 32.2 years (range 25-43), and the mean gestational age was 18 weeks (range [13][14][15][16][17][18][19][20][21][22]. The recorded mean in terval between abortion and death was 8 min (range 1-18) (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of using fetal tissues from spontaneous abortions was recently suggested by Thorne and Michejda [22] , The feasibility of fetal tissue collection and preparation depends on the occurrence of spontaneous abortions in hospitals. In fact, it is unlikely that fetuses aborted elsewhere could be collected correctly and sent to a facility that can prepare the fetal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Over 10 years ago we carried an epidemiological study on the incidence of spontaneous miscarriages [47]. This work provided important data to show that the number of miscarriages that could provide viable second trimester fetal tissue was very large.…”
Section: Comparative Study Of Stem Cells Derived From Various Sourcesmentioning
confidence: 99%
“…Also, another option is to secure fetal tis sue from spontaneous abortions, as dis cussed by Thorne and Michejda [22], They showed that the number of such events that occur in hospitals in the United States (pos sibly 750,000) are large enough to justify organized preparedness to use these tissues instead of those from elective abortions.…”
Section: Two Options For Actionmentioning
confidence: 99%